Social safety nets for food and nutritional security in India - Sudha Narayanan; Nicolas Gerber (University of Bonn, Center for Development Research (ZEF), 2016)
This paper brings together existing literature on the Mahatma Gandhi National Rural Employment Guarantee Act (MGNRGEA) and the Public Distribution System (PDS) in India, offering a narrative review of the evidence on impacts on food security, health and nutrition of beneficiaries. Both programs operate on a large scale and have the capacity to impact the factors leading to undernutrition. It is evident that despite the deficiencies in implementation, both the MGNREGA and the PDS are inclusive and reach the poor and the marginalized who are likely to also experience greater undernutrition and poor health. Data challenges have however prevented researchers from conducting studies that assess the ultimate impact of these two large-scale programs on health and nutrition. The evidence that exists suggests largely positive impacts indicating a clear potential to make these programs more nutrition sensitive not just by incorporating elements that would explicitly address nutritional concerns but also by directing specific attention to innovations that strengthen critical complementarities and synergies that exist between the two programs.
Keywords: H5; H7; I38; 330; social safety nets; India; complementarity and synergies; food and nutrition security; health